Safe Haskell | Safe-Inferred |
---|
- type Transform a b = forall m r. Monad m => Sink b m r -> Sink a m r
- mergeTransform :: Monad m => (Sink b m r -> Sink a m r) -> (Sink c m r -> Sink b m r) -> Sink c m r -> Sink a m r
- transformSink :: Monad m => (Sink b m r -> Sink a m r) -> Sink b m r -> Sink a m r
- transformSource :: (Source src, Monad m) => (forall r. Sink b m r -> Sink a m r) -> src m a -> SimpleSource m b
- (=$=) :: Monad m => (Sink b m r -> Sink a m r) -> (Sink c m r -> Sink b m r) -> Sink c m r -> Sink a m r
- (=$) :: Monad m => (Sink b m r -> Sink a m r) -> Sink b m r -> Sink a m r
- ($=) :: (Source src, Monad m) => src m a -> (forall r. Sink b m r -> Sink a m r) -> SimpleSource m b
Documentation
mergeTransform :: Monad m => (Sink b m r -> Sink a m r) -> (Sink c m r -> Sink b m r) -> Sink c m r -> Sink a m rSource
Merges two transforms into one.
transformSink :: Monad m => (Sink b m r -> Sink a m r) -> Sink b m r -> Sink a m rSource
Apply a transform to a sink.
transformSource :: (Source src, Monad m) => (forall r. Sink b m r -> Sink a m r) -> src m a -> SimpleSource m bSource
Apply a transform to a Source.
(=$=) :: Monad m => (Sink b m r -> Sink a m r) -> (Sink c m r -> Sink b m r) -> Sink c m r -> Sink a m rSource
Merges two transforms into one.